Quantum Character of Electromagnetic Langmuir Oscillations in Conventional Electron-Ion Plasma - Boris Alexandrovich Veklenko (International Journal of Optics)
It is shown that the low-temperature plasma near-thermodynamic equilibrium cannot be classical because of a quantum nature of the longitudinal electromagnetic field and electron interaction with Rayleigh-Jeans distribution of Langmuir waves. The theory requires introduction of a dimensionless quantum charge whose value is greater than unity leading to a liquid-like behavior of the plasma.